Automation and digitalization of processes in the management of service organizations - Trofimov, Ivan; Artykhov, Anton; Gostilovich, Aleksandr; Chizhov, Sergey (Revista Gestão & Tecnologia, 2023)
The study aims to research the process of digital transformation in service companies and examine current trends in the management of digital transformation processes in service companies, including in the sphere of the co-consumption economy. The study is conducted based on the personal practical experience of the authors in engaging in and organizing the process of digital transformation in Russian companies. The article successively considers current trends in the management of digital transformation processes for service companies, including those in the co-consumption economy. The authors conclude that the digital economy requires service company managers to be able to implement digital transformation projects. It is also argued that successful management of digital transformation demands that the full context and strategic goals of the company are taken into consideration